Manajemen Bencana Pemerintah Kabupaten Garut Studi Kasus: Letusan Gunung Papandayan Tahun 2008 - SARI, CICI WIDIAN; ., FITRIYAH; ADNAN, MUHAMMAD (Journal of Politic and Government Studies, 2016)
AbstractVolcanic eruption hazard is a threat with potentially catastrophic risks arevery high in Garut regency. Therefore, researchers want to know how disatermanagement of garut regency goverment in Papandayan volcano in 2008 as wellas how community involvement in this countermeasures of disaster..This study is a qualitative research that is a descriptive study using dataanalysis.This research is the ex post facto. Informants in this research is Tb AroHaq who is the section head of preventif BPBD Garut regency once volunteers inthe event of Papandayan volcano in 2008.The results shows that disaster management implementation ofpapandayan volcanic eruption in 2008 implemented in three stage is pre-disaster,disaster emergency response and post disaster. Paradigm developed in this disastercountermesuresis a preventive paradigm in which the change from an emergencyresponse to risk management.It is changing the way people to participate in thisdisaster countermeasures of all stage.Therefore, researcher suggests that governemnt together with the publicand private sector should coordinate to organize disaster management activities ofGarut regency and encourage preventive paradigm in countermeasures of disasterembodied in the form of policies, regulations and procedures of disaster remainsto tle lowest level of government.Keywords: Disater management, Garut regency government, Communityinvolvement, Papandayan volcano eruption in 2008